2017
DOI: 10.1063/1.4974077
|View full text |Cite
|
Sign up to set email alerts
|

An insight of p-type to n-type conductivity conversion in oxygen ion-implanted ultrananocrystalline diamond films by impedance spectroscopy

Abstract: The impedance spectroscopy measurements were used to investigate the separated contributions of diamond grains and grain boundaries (GBs), giving an insight of p-type to ntype conductivity conversion in O + -implanted ultrananocrystalline diamond (UNCD) films. It is found that both diamond grains and GBs promote the conductivity in O + -implanted UNCD films, in which GBs make at least half contribution. The p-type conductivity in O + -implanted samples is a result of H-terminated diamond grains, while n-type c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 49 publications
1
11
0
Order By: Relevance
“…Furthermore, an n−p-type transformation in Bi 4 V 2 O 11 might occur because of the implanted oxygen, leading to the coexistence of n-and p-type domains. 21 Thereby, a p−n-type photochemical homojunction could be constructed, where the Fermi-level (E f ) alignment of the p-and n-type domains emerges, creating a built-in field. 22 The photogenerated electrons and holes would separate effectively by means of migrating in opposite directions at the homojunction interface, 23 ulteriorly promoting the photocatalysis.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, an n−p-type transformation in Bi 4 V 2 O 11 might occur because of the implanted oxygen, leading to the coexistence of n-and p-type domains. 21 Thereby, a p−n-type photochemical homojunction could be constructed, where the Fermi-level (E f ) alignment of the p-and n-type domains emerges, creating a built-in field. 22 The photogenerated electrons and holes would separate effectively by means of migrating in opposite directions at the homojunction interface, 23 ulteriorly promoting the photocatalysis.…”
Section: Introductionmentioning
confidence: 99%
“…It is observed that the contact potential of samples increases with T a increasing, implying the loss of negative electron affinity at higher T a . [26] It is probably because of the absence of H-termination of nanocrystalline diamond grains when T a is above 800 o C. [27][28][29] The increasing numbers of conductive sites in samples C12900 and C121000…”
Section: Resultsmentioning
confidence: 99%
“…This value is in good consistent with those for the nitrogen-doped UNCD films reported in the literature [32], [33], which is strongly influenced by nitrogen quantity incorporated in the UNCD films. Moreover, the latter value was increased by raising the measurement temperature to be in the range of 50-150 meV [34], [35]. It was reported that π-bonded states associated with the GBs are the main reason for the n-type conduction in nitrogen-doped UNCD films [36].…”
Section: B Device Characterizationmentioning
confidence: 98%